APPROACHES AND INTERACTIVE METHODS IN FOREIGN LANGUAGE TEACHING (British Journal of Global Ecology and Sustainable Development, 2024)
Modern approaches and interactive methods are of great importance in the field of foreign language teaching. The processes of globalization, the development of communication technologies, and the expansion of international relations have increased the necessity of learning foreign languages. Today, foreign language teaching is not limited to just learning grammar and vocabulary; it also involves preparing students to apply the language in practice. This article provides detailed information about the approaches and interactive methods in foreign language teaching.